Can Job Training Decrease Women’s Self-Defeating Biases? : Experimental Evidence from Nigeria - Croke, Kevin; Goldstein, Markus; Holla, Alaka (World Bank, Washington, DC, 2017)
Occupational segregation is a central contributor to the gap between male and female earnings worldwide. As new sectors of employment emerge, a key question is whether this pattern is replicated. This paper examines this question by focusing on the emerging information and communications technology sector in Nigeria. Using a randomized control trial, the paper examines the impacts of an information and communications technology training intervention that targeted university graduates in five major cities. The analysis finds that after two years the treatment group was 26 percent more likely to work in the information and communications technology sector. The program appears to have succeeded only in shifting employment to the new sector, as it had no average impact on the overall likelihood of being employed. However, viewed through the lens of occupational segregation, the program had a surprising effect. For women who at baseline were implicitly biased against associating women with professional attributes, the likelihood that the program induced switching into the information and communications technology sector was more than three times as large than that of unbiased women. These results suggest that training programs can help individuals overcome self-defeating biases that could hamper mobility and reduce efficiency in the labor market.